Analysis of Factors Affecting Financial Management of Accounting Students During the Covid-19 Pandemic (Case Study on Accounting Students at Muhammadiyah University of Surakarta): Analisis Faktor-Faktor yang Mempengaruhi Pengelolaan Keuangan Mahasiswa Akuntansi pada Masa Pandemi Covid-19 (Studi Kasus pada Mahasiswa Akuntansi Universitas Muhammadiyah Surakarta) - SHOLIKHAH, ERVINA DENTA MAR'ATU; Arian, Kurnia Rina (Universitas Muhammadiyah Sidoarjo, 2022)
This study aimed to examine the effect of mental accounting, lifestyle hedonisme, socio-economic status of family, gender, and fintech payment on the financial management of accounting students at Muhammadiyah University of Surakarta. The analysis used in multiple regression analysis bu using SPSS (Statistical Package for Social Science) 21 version. The results of this study indicated that the mental accounting, lifestyle hedonisme, socio-economic status of family, and fintech payment had a positive and significant effect on the financial management og accounting students. While the variables gender didn’t have a positive and significant affect on the financial management og accounting students.